Editorial: Let there be light: Biological impact of light exposure in the laboratory and the clinic - Gonzalez, Monica M. C. (2018)
Light is a relevant environmental factor due to its role in the synchronization of mammalian biological rhythms driven by the master circadian clock, the suprachiasmatic nucleus (SCN) (1– 4). Although light exposure has obvious beneficial properties on the quality of life, different articles have highlighted the deleterious effects of certain artificial lighting conditions that might affect the health and wellbeing of human beings and laboratory animals. Indeed, we are exposed to artificial light during the night and, in addition, constant lighting conditions or altered photoperiods are tools frequently used in experimental animals, neglecting the fact that these environments might influence the integrity of the nervous system and endocrine, physiological and behavioral-dependent processes that rely on the activity of the biological clock.